On global order : power, values, and the constitution of international society - Hurrell, Andrew, 1955- (Oxford ; New York : Oxford University Press, 2007)
A clear and wide-ranging introduction to the analysis of global political order, this book offers engaging answers to the key questions of contemporary world politics.
Governing the globe -- The anarchical society revisited -- State solidarism and global liberalism -- Complex governance beyond the state -- Nationalism and the politics of identity -- Human rights and democracy -- War, violence, and collective security -- Economic globalization in an unequal world -- The ecological challenge -- One world? many worlds? -- Empire reborn? -- The state of international society and the pursuit of justice.
Includes bibliographical references (pages 319-347) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: International relations; International organization; International cooperation